News shocks: Different effects in boom and recession? - Maria Bolboaca; Sarah Fischer (Swiss National Bank, Study Center Gerzensee, 2019)
This paper investigates the nonlinearity in the effects of news shocks about technological innovations. In a maximally flexible logistic smooth transition vector autoregressive model, state-dependent effects of news shocks are identified based on medium-run restrictions. We propose a novel approach to impose these restrictions in a nonlinear model using the generalized forecast error variance decomposition. We compute generalized impulse response functions that allow for regime transition and find evidence of state-dependency. The results also indicate that the probability of a regime switch is highly influenced by the news shocks.
Keywords: E32; C32; C51; O47; 330; smooth transition vector autoregressive model; nonlinear time-series model; news shock; generalized impulse responses; generalized forecast error variance decomposition